Gender differences in perceptions and attitudes toward online shopping: A study of Malaysian consumers - Lim, Yet Mee; Cheng, Boon Liat *; Cham, Tat Huei; Ng, Caryn Kar Yan; Tan, J. X. (2019)
Despite the high potential of online shopping in Malaysian market, there is still a lack of understanding with regards to gender differences on online shopping behaviour. This research was conducted to determine the differences between male and female Internet users on their perceptions and attitudes toward online shopping. Data were collected from 500 respondents via social network website, Facebook. The results of the study revealed that men are more in favour of online shopping, have positive attitude towards web advertising, and perceive online shopping as more useful compared to women. On the other hand, women users perceive online shopping to be joyful than men. This research results have profound implications on online retailers and marketers.